Supporting the allocation of traumatized patients with a decision support system - Majchrzak, Tim A.; Ückert, Frank (Using social and information technologies for disaster and crisis management, 2013)
Supporting the Allocation of Traumatized Patients with a Decision Support System: 10.4018/978-1-4666-2788-8.ch011: In this paper, the authors present a business rules-based decision support system for the allocation of traumatized patients. The assignment of patients to
Gesehen am 20.06.2018